ANALISIS PENGARUH INFLASI DAN ASSET UNDER MANAGEMENT TERHADAP KINERJA REKSADANA SAHAM DI INDONESIA - Shafira Tasya Ramadhanti, (2022)
The research with title "Analysis of the Effect of Inflation and Asset Under Management on the Performance of Equity Mutual Funds in Indonesia" can be classified as a quantitative type of research which aims to prove the impact of inflation and asset under management on the performance of equity mutual funds in Indonesia. The object chosen in this study is stock mutual funds using a sample of 82 stock mutual fund products in the 2018-2020 period. The analytical technique used is Panel Data Regression Analysis using the Eviews 12 program. The results found from this study are that inflation has a significant effect and has a negative relationship on the performance of stock mutual funds, while asset under management has no effect on the performance of stock mutual funds